Review of the genus Carlschoenherria (Coleoptera: Scarabaeidae: Melolonthinae) of the Philippines - Calcetas, Orlando A. (Zootaxa, 2019)
The genus Carlschoenherria Bezděk, 2016 (Coleoptera: Scarabaeidae: Melolonthinae: Melolonthini) in the Philippines is reviewed. Three new species: Carlschoenherria adoradae Calcetas, new species, C. hadsallae Calcetas, new species, and C. gapudi Calcetas, new species are described, figured and compared with their close relatives. The following new combinations are proposed: Carlschoenherria palawana (Moser, 1915) new combination, C. philippinica (Brenske, 1894) new combination, C. argus (Burmeister, 1855) new combination, C. hastata (Arrow, 1938) new combination and C. vervex (Sharp, 1876) new combination. A new C. adoradae species-subgroup is proposed under the broader C. sulcipennis species-group. A key of the Carlschoenherria of the Philippines Islands, Malay Peninsula, Sumatra and Java is provided.